Insight Into the Prospects for RNAi Therapy of Cancer - Tian, Zhili; Liang, Guohui; Cui, Kunli; Liang, Yayu; Wang, Qun; Lv, Shuangyu; Cheng, Xiaoxia; Zhang, Lei (Frontiers in Pharmacology, 2021)
RNA interference (RNAi), also known as gene silencing, is a biological process that prevents gene expression of certain diseases such as cancer from the inside of the cell, bringing hopes and future to treatments, particularly genetic ones with accuracy, efficiency, and stability. However, challenges such as delivering to less accessible parts of the body and limiting toxic side effects are still encountered, for the imperative to reduce harmful effects on the noncancerous cell. Therefore, RNAi is a potential therapy with apparent merits and problems waiting to be addressed, in an effort to benefit future cases and patients. What is more, with the sudden outbreak of COVID-19, whether RNAi is capable of treatment will be discussed, in order to decrease current losses and cases. At the same time, the relationship between RNAi and tumor microenvironment (TME) is needed to be considered, for the specialty and feature it possess in optimum temperature, pH value and the optimal concentration of drugs. Generally, this review aims to introduce the mechanism of RNAi and the general applications by exploring the current challenges of RNAi therapy, listing some of the delivery systems concerning cancer to provide current solutions and drug information. It is worthy to mention that delivery systems such as lipid-based delivery system, exosomes have brought great potential to RNAi therapy, deal to the low immunogenicity and high cellular affinity. A deeper understanding of the mechanism and challenge underlying RNAi therapy in cancer provide us new strategies for RNAi drug development.